Pengaruh Model Pembelajaran ARIAS terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas II SD Negeri 228 Palembang - Dhea Kharisma; Ramanata Disurya; Tanzimah Tanzimah (Journal on Education, 2023)
The formulation of the problem in this study is whether there is an effect of the ARIAS learning models on student learning outcomes in Mathematics class II SD Negeri 228 Palembang. The purpose of this study was to determine whether there is an effect of the ARIAS learning model on student learning outcomes in Mathematics class II SD Negeri 228 Palembang. The study population was all grade II students of SD Negeri 228 Palembang which amounted to 68 students. The method used in this research is experimental. The techniques used were test and documentation techniques. Based on the learning outcomes test, it is known that the experimental class test results with the highest score of 100 and the lowest score of 60 averaged 86.84. While the control class test results with the highest score of 80 and the lowest score of 30 averaged 60.42. The calculation results obtained tcount = 7.426 and ttable = 1.683 significant level = 0.05. Means tcount > ttable, then Ha is accepted. Indicating that there is an effect of the ARIAS learning models on student learning outcomes in grade II mathematics subjects at SD Negeri 228 Palembang.